2011
DOI: 10.1177/1748006x11417503
|View full text |Cite
|
Sign up to set email alerts
|

Wind generation’s contribution to supporting peak electricity demand – meteorological insights

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…A typically high-demand/low-wind winter in Ireland shows higher frequencies of Greenland and Atlantic blocking regimes. This is consistent with the findings of previous studies (Brayshaw et al 2011b, Grams et al 2017, Thornton et al 2017. Relating the findings to teleconnection patterns, the Greenland Blocking regime strongly resembles an NAO negative state, whilst a positive EA resembles the Atlantic Blocking regime.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A typically high-demand/low-wind winter in Ireland shows higher frequencies of Greenland and Atlantic blocking regimes. This is consistent with the findings of previous studies (Brayshaw et al 2011b, Grams et al 2017, Thornton et al 2017. Relating the findings to teleconnection patterns, the Greenland Blocking regime strongly resembles an NAO negative state, whilst a positive EA resembles the Atlantic Blocking regime.…”
Section: Discussionsupporting
confidence: 92%
“…This combination could have resulted in strain on the electricity supply system but Leahy and Foley (2012) conclude that, in fact, the impact on electricity demand in Ireland was lower than expected due to coincidental holidays and a period of economic recession. Brayshaw et al (2011a) found that during a very cold and calm spell in January 2010, very low aggregate wind generation for the whole of GB (dominated by Scottish wind farms) coincided with high demand for electricity. The cold spells of the following winter of 2010-2011 (10-11) were actually more severe in terms of persistent low air temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future, we hope to link this research with reanalysis-based estimates of electricity demand (as outlined in Ref. [33]), thus enabling a more thorough investigation of the above power system impacts.…”
Section: Discussionmentioning
confidence: 99%
“…On daily to weekly timescales GB wind power capacity has been related to synoptic scale (approximately 1000 km) weather events termed regimes, with zonal (west-east) regimes resulting in highest aggregate wind power generation, and blocked regimes resulting in lowest aggregate wind power generation [14,15]. There is general consensus in the literature that GB peak demand is associated with an area of high pressure in the vicinity of GB, consistent with low temperatures over GB [14,[16][17][18]. These previous studies of climate-energy interactions are, however, typically limited in two key respects.…”
Section: Introductionmentioning
confidence: 99%